PELATIHAN DAN PENDAMPINGAN BUDIDAYA DAN PENGOLAHAN BAWANG MERAH ASAL TRUE SHALLOT SEEDS (TSS) DI DESA BRANG KOLONG KECAMATAN SUMBAWA - Ihlana Nairfana; Aluh Nikmatullah; Topan Rahmatul Iman (Universitas Mataram, 2023)
Shallot farmers from Brang Kolong Village, Sumbawa Regency, have been cultivating shallots from bulbs. The main problem faced by farmers is the decreased productivity of shallots even though the planting area has increased from year to year. With an increase in the area for planting shallots, automatically the need for seeds from tubers will also increase. Therefore, cultivating shallots other than bulbs is very much needed, one of which can be achieved by planting shallots from seeds or what is known as TSS (True Shallot Seeds). ). Other problems faced by partners are high postharvest weight losses, and also the size of shallot bulbs that do not vary. This affects the selling value of shallots in the market. Therefore, training and assistance is carried out on shallot cultivation through the TSS method, good postharvest handling and processing of low grade shallot yields to become onion chili paste and crispy fried shallots. The stages of community empowerment include the preparation stage, FGD socialization of work programs with partners, training and technical assistance for shallot cultivation using the TSS method, post-harvest training and new product development from rejected onion bulbs. The output of this activity was an increase in partners' knowledge regarding aspects of shallot cultivation and processing from TSS which was marked by an increase in the average pre-test score of 55% to 87% in the post-test.